Pendidikan Anak Usia Dini Pada Lingkungan Keluarga - Nanik Rahayu; Saniyya Putri H; Mashita Nunlehu; Mia Sumiani Madi Ludgardis; Agus Sudarya (Publikasi Indonesia, 2022)
Children have a very important role because they will be the next generation of the nation. then the development of children should be started as early as possible so that in the future children can have good self-quality. The best time to do children's education is at the golden age of 1-6 years the golden age is the right time to start optimizing education for children to be able to make children develop optimally. The type of education carried out is intellectual and spiritual education with the form of education using storytelling. The goal of researchers is to inform readers about early child education in the family, the method used is a review of litelature or literature that researchers have concluded that early child education at home is a long range education for children during their lifetime. Pendidikan anak usia dini